Excited/Ground State of Kekulé di-radical Material Bisphenalenyl - Dr Ke Wang; Dr Koji Yokoyama; Ms Jie Peng; Dr Alan Drew; Dr Junzhi Liu (ISIS Facility, 2019)
Kekulé di-radical (KDR) with two radical centers of independent spins has a low-spin ground state (singlet S0 with antiparallel spins), and interestingly high-spin triplets (T1) can be thermally activated and populated at high temperature to advance the room-temperature spin-active properties of KDR materials. Hence, it is important to microscopically study the electronic structures of S0 and T1 of KDRs. We plan to use photo-pump muon-probe muSR to learn photo induced effect on muSR spectra at 10K, where the ground states are mostly populated before photo excitation, to demonstrate that muon can the study the differences in electronic structures of T1 and S0 in KDR materials, while other methods may not resolve signals due to broadening effects in solids. Sample was chosen due to its symmetry and simplicity. Relevant muSR spectra in ground state has been done. This is a follow-up work.
Keywords: STFC ISIS Neutron and Muon Data